KG Resource Pack Mathematics - Term II - THE CITY SCHOOL (PAKISTAN THE CITY SCHOOL)
This resource pack provides activities and exercises designed to support the development of mathematical skills in kindergarten students during Term II.
Includes activities and exercises for kindergarten mathematics
For kindergarten-aged children
Keywords: Mathematics - Study and teaching (Kindergarten)-Early childhood education